Green Stream Movement : Revitalisasi Sungai Deli Melalui Kolaborasi Mahasiswa dan Dosen - Hendra Jonathan Sibarani; Hana Salsabila Lubis; Debora Tambunan; Victor Maruli Pakpahan; Sungguh Ponten Pranata; Yenni Martok; Dewi Rafiah Pakpahan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
River cleanliness is a very important environmental issue, especially in densely populated areas that are vulnerable to water pollution. The “Green Stream Movement” program is a community service initiative carried out by a team of students and lecturers to revitalize the condition of the Deli River around the Medan-Marelan area. This activity includes community education, river cleaning, and innovation of waste sorting systems around the river flow. The purpose of this program is to increase environmental awareness of residents and build a sustainable system to maintain river cleanliness. The results of the program show an increase in community participation and a decrease in the amount of waste in the river area by. Collaboration between students, lecturers, and the community has proven effective in creating real changes in the environment